Heidihuangwan alleviates renal fibrosis in rats with 5/6 nephrectomy by inhibiting autophagy - Li, Ying-Ying; Tian, Zeng-Hui; Pan, Guang-Hui; Zhao, Ping; Pan, De-Jun; Zhang, Jun-Qing; Ye, Li-Ying; Zhang, Fa-Rong; Xu, Xiang-Dong (Frontiers in Pharmacology, 2022)
Renal fibrosis is a common pathway for the progression of various chronic kidney diseases, and the formation and deterioration will eventually lead to end-stage renal failure, which brings a heavy medical burden to the world. HeidihuangWan (HDHW) is a herbal compound with stable and reliable clinical efficacy in the treatment of renal fibrosis. In this study, we aimed to investigate the mechanism of HDHW to improve renal fibrosis. Wistar rats were randomly divided into normal control group, 5/6 Nephrectomy group, astragaloside IV (AS-IV) group, HDHW group, and HDHW + IGF-1R inhibitor (JB1) group. Except for the normal control group, the rat renal fibrosis model was established by 5/6 nephrectomy and intervened with drugs for 8 weeks. Blood samples were collected to evaluate renal function. Hematoxylin-Eosin (HE), Periodic Acid-Schiff (PAS), Modified Masson's Trichrome (Masson) staining to evaluate the pathological renal injury, and immunohistochemistry and Western blotting to detect the protein expression of renal tissue. The results showed that HDHW was effective in improving renal function and reducing renal pathological damage. HDHW down-regulated the levels of fibrosis marker proteins α-smooth muscle actin (α-SMA), Vimentin, and transforming growth factors – β（TGF-β）, which in turn reduced renal fibrosis. Further studies showed that HDHW down-regulated the expression of autophagy-related proteins Beclin1 and LC3II, indicating that HDHW inhibited autophagy. In addition, we examined the activity of the class I phosphatidylinositol-3 kinase (PI3K) / serine-threonine kinase (Akt) /mTOR pathway, an important signaling pathway regulating autophagy, and the level of Insulin-like growth factor 1 (IGF-1), an upstream activator of PI3K/Akt/mTOR. HDHW upregulated the expression of IGF-1 and activated the PI3K/Akt/mTOR pathway, which may be a vital pathway for its inhibition of autophagy. Application of Insulin-like growth factor 1 receptor (IGF-1R) inhibitor further confirmed that the regulation of autophagy and renal fibrosis by HDHW was associated with IGF-1-mediated activation of the PI3K/Akt/mTOR pathway. In conclusion, our study showed that HDHW inhibited autophagy by upregulating IGF-1 expression, promoting the binding of IGF-1 to IGF-1R, and activating the PI3K/Akt/mTOR signaling pathway, thereby reducing renal fibrosis and protecting renal function. This study provides support for the application and further study of HDHW.